Heavy metals in soils and edible tissues of Lepidium meyenii (maca) and health risk assessment in areas influenced by mining activity in the Central region of Peru - Orellana Mendoza, Edith (2021)
Heavy metal contamination of soil and agricultural products is an environmental problem, has an adverse effect on the quality of food crops, and is a danger to food security and public health. The concentration of arsenic (As), cadmium (Cd), lead (Pb), iron (Fe) and zinc (Zn) in surface soils and edible hypocotyls tissues of two ecotypes of Lepidium meyenii Walpers (maca) was evaluated in three districts of the Junín province, Peru. In addition, the risk to human health due to exposure to heavy metals from maca consumption was evaluated. Soil samples and maca hypocotyls were collected in areas influenced by mining and metallurgical activity. The mean concentration of Cd (0.32 ± 0.23 mg/kg) and Pb (0.20 ± 0.12 mg/kg) in maca samples exceeded the values established by the Food and Agriculture Organization and the World Health Organization. The bioconcentration factor was less than 1. The estimated daily intake of each metal was below the oral reference dose. The hazard quotient and hazard index were less than 1, it is unlikely to cause non-cancer adverse health outcome. The cancer risk for As and Cd was higher than the tolerable limit (1 × 10−6) in children and adults. In the district of Ondores, the cancer risk for As in children was higher than the acceptable limit (1 × 10−4). Residents of the Ondores district would be more exposed to As and Cd from consumption of maca hypocotyls. It is very important to carry out continuous monitoring of other toxic metals in different ecotypes of maca (red, black, yellow, purple, creamy white, pink) in order to evaluate the variation in the accumulation of heavy metals and the level of toxicity of each metal between ecotypes.